Nodal Marginal Zone Lymphoma with Aberrant CD10 Expression: A Case Report and Literature Review - Song, Buer; Zhang, Nan; Zheng, Yan; D’Angelis, Christopher A.; Cai, Donghong (North American Journal of Medicine and Science, 2013)
CD10+ nodal marginal zone lymphoma is very rare, with only one case report in the English literature currently. Here we report a case of nodal marginal zone lymphoma with strong CD10 expression occurring in a 76 year-old female with extensive lymphadenopathy. The lymph node biopsy showed a population of small lymphocytes diffusely infiltrating into the interfollicular areas and colonizing disrupted follicles. Immunohistochemical staining revealed that these small lymphocytes were positive for CD20, PAX-5, Bcl-2 and bright CD10. Bcl-6, Cyclin D1 and CD43 were negative in this population of cells. In contrast, the residual germinal center B-cells demonstrated expression of CD10 and Bcl-6 and negative staining for Bcl-2. Flow cytometry study demonstrated a CD10+CD20+ kappa-restricted B-cell lymphoma. FISH studies for translocation of IgH, Bcl-2 and Bcl-6 were negative. Therefore, a diagnosis of CD10+ nodal marginal zone lymphoma was established. This rare disease entity illustrates a possible diagnostic pitfall within the group of mature small B-cell lymphomas, especially for follicular lymphomas with a diffuse pattern. The clinical significance of CD10 positivity in nodal marginal zone lymphomas is unknown. More cases and additional clinical follow up are required to address this question.